Summa Technologiae - Lem, Stanisław (Book collections on Project MUSE., 2013)
In Summa Technologiae, Stanislaw Lem produced an engaging and caustically logical philosophical treatise about human and nonhuman life in its past, present, and future forms. After five decades this work has lost none of its intellectual or critical significance, resonating with contemporary debates about information and new media, the life sciences, and the emerging relationship between technology and humanity.